Navigating the Digital Diplomacy Frontier: Multilateral Cooperation in Al Regulation at the UN and EU Levels (International relations and international law Journal, 2024)
This paper delves into the critical role of multilateral cooperation in regulating artificial intelligence (AI) at both the United Nations and European Union levels, highlighting the realm of digital diplomacy. Amidst the ever-evolving landscape of global governance, it focuses on strategies within UN and EU frameworks to oversee AI development. The research aims to shed light on the challenges and opportunities inherent in regulating AI and emphasizes the importance of collective action in formulating effective regulatory measures. By analyzing the intersection of AI, international relations, and governance, the study seeks to contribute to the ongoing discourse on shaping ethical and strategic policies in the digital age. Methodologically, the research employs a comprehensive review of existing literature, policy documents, and multilateral initiatives related to AI regulation.The findings highlight the complexities of regulating AI in a rapidly evolving technological landscape and underscore the need for multilateral cooperation to address emerging challenges effectively. In terms of value, this research contributes to advancing the understanding of AI governance and digital diplomacy, providing insights into the evolving dynamics of multilateral cooperation in regulating emerging technologies. Practically, the findings offer actionable insights for policymakers and stakeholders involved in AI regulation, highlighting the importance of coordinated efforts to address regulatory gaps and promote responsible AI development.Key words: artificial intelligence, multilateral cooperation, digital diplomacy, аrtificial intelligence governance, United Nations, European Union.